Analisis Implementasi Peraturan Daerah Provinsi Banten Nomor 5 Tahun 2018 Tentang Penyelengaraan Pembangunan Ketahanan Keluarga Di DP3AKKB - Reviana Utari; Eli Apud Saepudin; Rizki Amilia (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Family resilience is a strategic foundation for achieving sustainable human development. However, the implementation of Banten Province Regional Regulation Number 5 of 2018 concerning Family Resilience Development has encountered various challenges, including limited inter-agency coordination, unequal program implementation, inadequate human resources, and low community participation. This study aims to analyze the implementation of the Regional Regulation at the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3AKKB) of Banten Province. The research employed a qualitative descriptive approach using interviews, observations, and document analysis. Data were analyzed through data reduction, data presentation, and conclusion drawing, while validity was ensured through source triangulation. The findings indicate that policy implementation has generally been carried out through family empowerment, family planning, and family quality improvement programs. Nevertheless, communication among stakeholders, resource availability, bureaucratic coordination, and policy implementers' commitment have not been fully optimized, resulting in uneven achievement of policy objectives across districts and municipalities. The study concludes that strengthening cross-sector collaboration, improving institutional capacity, enhancing human resources, and increasing community participation are essential to improve the effectiveness of family resilience development in Banten Province.